Impact of COVID-19 Shocks on the Volatility of Stock Markets of Emerging Economies - Muhammad Ahsan Ali; Muhammad Nazam; Attaullah; Faiz Rasool; Muhammad Faheem Ullah (International Journal of Business and Economic Affairs, 2023)
The COVID-19 Outbreak has increased volatility in Pakistan relative to other growing countries on international stock markets. This study examines this phenomenon using the Threshold Generalized Autoregressive Conditional Heteroscedasticity (TGARCH) model. This daily time-dependent information flows into the market for PSX-listed equities are explained. This research aims to provide empirical evidence in favor of the TGARCH specification. Through COVID-19, we observed that the volatility of returns from developing countries significantly affects the Pakistani stock market, utilizing data from a selection of countries’ stock markets at their respective closing times between January 1, 2015, and April 30, respectively, 2022. Descriptive statistics, Correlation, and TGARCH Model were used to find the desired outcomes. In addition, findings indicate that the Bombay Stock Exchange (BSE) and Shanghai Stock Exchange (SSE) play a pivotal role in understanding the volatility of Pakistan, a developing nation. Despite the existence of the leverage effect during COVID-19, we were unable to find any correlation between the performance of stocks on the Dhaka Stock Exchange (DSE) and volatility on the Karachi Stock Exchange (KSE). The study will provide more information to investors, brokers and market players about the volatility of the financial markets.